Manajemen Zero Antara Standard Kualitas Dan Dimensi Kualitas - Fahada, Nazli (ALACRITY : Journal of Education, 2024)
This study aims to explore the concept of zero management in the context of quality standards and related quality dimensions. The research method used is theoretical research, which aims to develop a conceptual framework and theoretical understanding of zero management. The quality standards and quality dimensions used in this study are derived from existing literature. The results of the research indicate that zero management has significant potential to improve product and process quality through the elimination of defects and operational efficiency. The study also finds that the successful implementation of zero management is highly dependent on organizational commitment, adequate training, and the use of appropriate quality management tools. The conclusion of this study is that integrating zero management with strict quality standards and a deep understanding of quality dimensions can lead to significant improvements in overall organizational performance. This research contributes theoretically by offering a new perspective on how zero management can be applied and optimized in managerial practice.